2014
DOI: 10.1016/j.radonc.2014.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 E7 oncoprotein causes a delay in repair of DNA damage

Abstract: Background and Purpose Patients with Human papillomavirus related (HPV+) head and neck cancers (HNCs) demonstrate improved clinical outcomes compared to traditional HPV negative (HPV−) HNC patients. We have recently shown that HPV+ HNC cells are more sensitive to radiation than HPV− HNC cells. However, roles of HPV oncogenes in regulating the response of DNA damage repair remain unknown. Material and Methods Using immortalized normal oral epithelial cell lines, HPV+ HNC derived cell lines, and HPV16 E7-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 36 publications
6
70
1
Order By: Relevance
“…A DNA-damage/ repair response has been previously described in papillomavirus infection. 29 We did not observe γH2AX-and/or p53-positive cells in the decidua of HPV negative cases. However, the strongest signal for HPV was identified in the endometrial epithelium ( Figure 3, photomicrograph a HPV L1 IHC), with both strong endometrial cell cytoplasmic and nuclear staining using HPV-CISH (Figure 3, photomicrographs b and c).…”
Section: Hpv Detection In the Decidua And Endometriumcontrasting
confidence: 51%
See 1 more Smart Citation
“…A DNA-damage/ repair response has been previously described in papillomavirus infection. 29 We did not observe γH2AX-and/or p53-positive cells in the decidua of HPV negative cases. However, the strongest signal for HPV was identified in the endometrial epithelium ( Figure 3, photomicrograph a HPV L1 IHC), with both strong endometrial cell cytoplasmic and nuclear staining using HPV-CISH (Figure 3, photomicrographs b and c).…”
Section: Hpv Detection In the Decidua And Endometriumcontrasting
confidence: 51%
“…We also observed an appropriate host response of DNA damage/repair and p53 activation, which was consistent with that previously described for papillomavirus infection. 29 To the best of our knowledge, this is the first study to describe in situ morphology of placental HPV infection and associated adverse clinical events, although further investigation is required to prove HPV is the etiologic agent. However, the popular assertion that HPV infection is of no clinical consequence in pregnancy maybe incorrect in light of our findings.…”
Section: Discussionmentioning
confidence: 90%
“…Increased levels of Rad51 have been documented in a wide range of human tumors, including HPV-positive head and neck cancer cell lines, as well as HPV-positive cervical cancer lines (42,72). Moreover, increased expression of Rad51 is correlated with increased genomic instability through an elevation in spontaneous and aberrant HR (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Park et al demonstrated that expression of HPV16 E7 in oral keratinocytes is sufficient to increase protein levels of Rad51 (42). To determine if HPV31 E7 is also capable of increasing the levels of Rad51, as well as BRCA1, we examined HFKs retrovirally transduced and stably expressing HPV31 E6, E7, or E6/E7 in combination.…”
Section: Homologous Recombination Factors Rad51 and Brca1 Are Increasmentioning
confidence: 99%
“…7,8 Various OSCC cell lines have been established but only a few HPV positive OSCC cell lines are available for in vitro study. [9][10][11] In this study, we established and characterized cell lines from the HPV positive OSCC of 2 patients. Corresponding HPV positive cell lines were subsequently generated from nodal metastases following xenografting of these cell lines into nude mice.…”
Section: Introductionmentioning
confidence: 99%